COVID‐19 restrictions increased perceptions of social isolation for older people discharged home after rehabilitation: A mixed‐methods study. (10th March 2022) - Hogan, Georgia; Taylor, Nicholas F.; Robins, Leslie; Callisaya, Michele L.; Snowdon, Megan; Moran, Chris; Snowdon, David A.
Abstract: Objective: To explore older persons' perceptions of the impact of COVID‐19 restrictions on participating in community activities after discharge from inpatient rehabilitation. Methods: Mixed‐methods study design. Participants were older adults who were discharged home following inpatient rehabilitation. Interviews were conducted with 70 participants, with a variety of diagnoses, 8 weeks after discharge from inpatient rehabilitation. Frequency of participation in domestic, leisure/work and outdoor activities was measured using the Frenchay Activities Index (FAI). Qualitative analysis was completed using qualitative content analysis and triangulated with FAI scores. Results: In all, 70 older adults (mean age: 73.0 years, SD: 9.9; 59% female) participated in the study. The overarching theme was that participants felt socially isolated following discharge from rehabilitation, with COVID‐19 restrictions increasing perceptions of social isolation and complicating their return to participating in community activities. The four categories informing the overarching theme were as follows: physical health was the primary limitation to participation in community activities; COVID‐19 restrictions limited participation in social activities and centre‐based physical rehabilitation; low uptake of videoconferencing to facilitate socialisation and rehabilitation; and reduced incidental physical activity. Mean FAI score was 21.2 (SD 7.8), indicating that participants were moderately active. Participants most commonly performed domestic activities (mean: 10.0, SD: 4.1), followed by outdoor activities (mean: 6.6, SD: 3.5) and leisure/work activities (mean: 4.5, SD: 2.5). Conclusions: COVID‐19 restrictions exacerbated perceptions of social isolation and the limitations already imposed by poor physical health after discharge from rehabilitation. The findings highlight the need for rehabilitation that addresses the psychological and social dimensions of community reintegration.